Powerful Patens in the Anglo-Saxon Medical Tradition and Exeter Book Riddle 48 - Cavell, M (Springer Verlag, 2016)
This article discusses Exeter Book Riddle 48 in light of its proposed solutions. While commonly solved as either “chalice” or “paten,” I argue that the riddle points toward the latter solution (OE husel-disc). This riddle is usually read in relation to its counterpart, Riddle 59, which scholarly consensus solves as “chalice” (OE calic or husel-fæt). However, Riddle 48 should be analysed in its own right, especially given evidence from the medical tradition that prescribes writing on patens and performing psalms and other prayers over them in order to cure sickness. It is to this practice and to the psalms that Riddle 48 gestures in its use of the term galdorcwide (incantation), as well as the direct quotation that appeals to God to heal the speaker.